EXPLORING INNOVATIVE ALTERNATIVE ASSESSMENT METHODS IN ELT: A STUDY ON THE INTEGRATION OF INFORMATION TECHNOLOGY - Aini, Nur; Asari, Slamet (English Review: Journal of English Education, 2024)
Innovative alternative assessment currently attracts an adequate attention since it alternates conventional assessment. The fast growth of technology provides chances to integrate this type of assessment into it. Through an examination of technology integration into the usage of innovative alternative assessment, this study seeks to advance our understanding of how to measure student learning outcomes accurately, which will improve teaching and learning. A questionnaire, observation, and interview were used to gather data from 65 teachers and 152 junior and senior high school students. The data was then combined with quantitative and qualitative methodologies using descriptive statistics and qualitative analysis. The finding indicated that the integration of information technology with its various platforms on innovative alternative assessment methods was perceived positively both by teachers and students. The data presented illustrates the perceived efficacy and acceptance of innovative alternative assessment methods facilitated by information technology, as well as the challenges and barriers encountered in integrating these assessments into existing learning environments. Some of the challenges and barriers that arose were mostly related to the exploitation of technology resources, access to them, and the absence of a suitable technological infrastructure for the purpose of discovering innovative alternative methods of assessment.